Diving into Math Success for Discipline and Interest Propel Sixth-Graders: Menyelami Kesuksesan Matematika untuk Mendorong Kedisiplinan dan Minat Siswa Kelas Enam - Arisandi, Desi; Wardana, Mahardika Darmawan Kusuma (Indonesian Journal of Innovation Studies, 2024)
<div class="min-h-[20px] text-message flex flex-col items-start whitespace-pre-wrap break-words [.text-message+&]:mt-5 juice:w-full juice:items-end overflow-x-auto gap-3" dir="auto" data-message-author-role="assistant" data-message-id="7bd1d5f6-6ad7-4359-b65a-35fe2e2eeaa1"> This study examines the relationship between learning discipline, interest in learning, and Mathematics learning outcomes among sixth-grade students at SDN Bulang, using a quantitative correlational approach. Data collected from 35 students through questionnaires and report card assessments were analyzed using SPSS v25. Results indicate a significant correlation between learning discipline, interest in learning, and Mathematics learning outcomes, with correlation coefficients of 0.747 (p=0.003) and 0.909 (p=0.001), respectively. These findings highlight the importance of cultivating both learning discipline and interest in learning to improve Mathematics performance among sixth-grade students, suggesting implications for educational practice and policy. Highlight: Correlation: Learning discipline, interest impact Mathematics outcomes. Quantitative study: 35 sixth graders' data analyzed using SPSS. Emphasizes fostering discipline, interest to enhance Mathematics performance. Keyword: Learning discipline, Interest in learning, Mathematics learning outcomes, Sixth-grade students, Quantitative correlational study